West Bank and Gaza Student Assessment : SABER Country Report 2013 - World Bank Group (World Bank, Washington, DC, 2016)
The West Bank and Gaza has focused on increasingstudent learning outcomes by improving the quality ofeducation in the country. An effective student assessment system is an important component of efforts to improve education quality and learning outcomes as itprovides the necessary information to meetstakeholders’ decision-making needs. In order to gain abetter understanding of the strengths and weaknesses ofits existing assessment system, the West Bank and Gaza decided to benchmark this system using standardized tools developed under the World Bank’s Systems Approach for Better Education Results (SABER) program. SABER is an evidence-based program to help countriessystematically examine and strengthen the performanceof different aspects of their education systems.The goal of SABER-Student Assessment is to promote stronger assessment systems that contribute to improved education quality and learning for all.